2009 IEEE International Conference on Communications 2009
DOI: 10.1109/icc.2009.5198824
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Dynamic Narrowband On-Body to Off-Body Area Channel

Abstract: A characterization of the dynamic narrowband onbody to off-body area channel is presented based on realtime measurements of the time domain channel response at carrier frequencies near the 900MHz and 2400MHz Industrial, Scientific and Medical (ISM) bands. A statistical characterization is presented of received signal amplitude when the subject's body is standing and walking, transmitted from the body to a receiver, Rx, off the body, with various orientations of the subject's body with respect to the receiver, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(26 citation statements)
references
References 10 publications
0
26
0
Order By: Relevance
“…Overlayed on each empirical PDF is the PDF of the best fit for four distributions. 6 It is noteworthy that in all these cases the best fits are either Weibull or Gamma distributions; in all cases, the best-fitting distributions, with parameters given in Table 2, provide good fits, as evidence in the figures for on-body measurements. It is of special note that in Fig.…”
Section: Agglomerate-data First-order Statistical Analysis-resultsmentioning
confidence: 85%
“…Overlayed on each empirical PDF is the PDF of the best fit for four distributions. 6 It is noteworthy that in all these cases the best fits are either Weibull or Gamma distributions; in all cases, the best-fitting distributions, with parameters given in Table 2, provide good fits, as evidence in the figures for on-body measurements. It is of special note that in Fig.…”
Section: Agglomerate-data First-order Statistical Analysis-resultsmentioning
confidence: 85%
“…The measurements were conducted in an anechoic chamber, and Lognormal and Ricean distributions were used to model the path-loss. In [7], similar studies were conducted in an indoor environment where Lognormal distribution proved to be a good fit in describing the normalized signal amplitude. Further studies were conducted in [8] in which also the impact of antenna polarization on channel characteristics was investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Unlike the models in [6][7][8], which are purely empirically based and applicable only in the environments similar to the measurement site; we propose a more accurate physicalstatistical based channel model for off-body communications. Generally, physical-statistical models are more accurate than merely empirical models as they rely on electromagnetic based methods for calculating the needed model parameters.…”
Section: Introductionmentioning
confidence: 99%
“…For several years, many efforts have been made to identify the propagation characteristics in on-to-off body communication [1][2][3][4]. In indoor environments, the log-normal and Rayleigh distributions provide good fit to the on-to-off body channels for standing and for walking, respectively [1].…”
Section: Introductionmentioning
confidence: 99%
“…In indoor environments, the log-normal and Rayleigh distributions provide good fit to the on-to-off body channels for standing and for walking, respectively [1]. Smith et al [2] showed that the on-to-off body channels for sleeping persons follow the Gamma distribution.…”
Section: Introductionmentioning
confidence: 99%